Characterization of isolated from stool specimens of diarrhea patients in Taizhou, China during 2020–2023 - Ding Ding; Yi Jiang; Yajing Lin; Ting Zhang; Jiejie Guo; Tian Jiang; Linyao Huang; Jianxin Yan; Long He (SAGE Open Medicine)
Purpose: This study aimed to investigate the pathogenic characteristics of Vibrio parahaemolyticus in Taizhou City, China, to provide a scientific basis for the diagnosis and control of Vibrio parahaemolyticus in the region. Methods: Bacterial strains were isolated from stool specimens of diarrheal patients at the First People’s Hospital of Wenling City. The virulence genes, serotypes, and antibiotic susceptibility of these strains were determined. Results: From June 1, 2020 to May 31, 2023, a total of 97 strains of Vibrio parahaemolyticus were isolated from stool specimens of diarrheal patients at the First People’s Hospital of Wenling City. The results of virulence gene detection showed that 87.6% of the strains were thermostable direct hemolysin (TDH; tdh ) + , thermolabile hemolysin ( tlh ) + , and tdh -related hemolysin ( trh ) − , 11.3% were tdh − tlh + trh − , and 1.0% were tdh + tlh + trh + . Six different serotypes were identified, with O3:K4 and O4:K4 being the most common, accounting for 42.3% and 32.0%, respectively. The other serotypes identified were O3:K6, O4:K8, and O1:KUT, accounting for 11.3%, 10.3%, and 3.1%, respectively. Furthermore, the results of antimicrobial susceptibility tests showed that most strains were sensitive to the tested drugs, while some strains exhibited resistance to cefuroxime (32.6%) and cefazolin (43.6%). Conclusion: The majority of the isolated Vibrio parahaemolyticus strains carried the tdh gene, and the O3:K4 serotype dominated in Taizhou City from 2020 to 2023, followed by the O4:K4 serotype. Furthermore, some strains exhibited resistance to cefuroxime and cefazolin.